Innervation of the southern green stink bug [Nezara viridula (L.) (Hemiptera: Pentatomidae)] stylet bundle. (January 2022) - Esquivel, Jesus F.; Droleskey, Robert E.; Harvey, Roger B.
Abstract: The southern green stink bug, Nezara viridula (L.) (Hemiptera: Pentatomidae), continues to threaten high-value cash crops, including cotton. Earlier reports confirmed ingestion and transmission of disease-causing pathogens of cotton, including elucidation of the dimensions for the food and salivary canals of the southern green stink bug stylet bundle. During this earlier work, innervation of the stylet bundle was observed. Here, we present the first imagery and descriptions of the innervations (i.e., dendrites) within the southern green stink bug stylets. Two types of dendrites innervate each mandibular stylet, and the number of dendrites differed depending on location. Within the head, six dendrites (3 within a thick-walled and 3 within a thin-walled dendrite sheath) are present in each mandibular stylet; only 3 dendrites within a thin-walled sheath are present at the most distal labial segment. Transmission electron microscopy (TEM) suggests innervation of the maxillary stylets, and the presence of stained tissue within the dendritic canal of the maxillary stylets was observed via light microscopy, thereby supporting the TEM analyses. These new observations regarding types and spatial differences in numbers of dendrites within the mandibular stylets – and the new revelation of innervation within maxillary stylets – improve the current knowledge base regarding internal stylet morphology and feeding mechanics. Highlights: Innervation of the southern green stink bug stylets is described. Two types of nerve bundles are present in each mandibular stylet. The number of nerve bundles within each mandibular stylet varies based on location. Contrary to current dogma, maxillary stylets also appear to possess nerve bundles.